Variability in temperature dependence of stem CO2 efflux from Norway spruce trees. (7th February 2018) - Darenova, Eva; Acosta, Manuel; Pokorny, Radek; Pavelka, Marian
Abstract: This study presents results from continuous measurements of stem CO2 efflux carried out for seven experimental seasons (from May to October) in a young Norway spruce forest. The objectives of the study were to determine variability in the response of stem CO2 efflux to stem temperature over the season and to observe differences in the calculated relationship between stem temperature and CO2 efflux based on full growing season data or on data divided into periods according to stem growth rate. Temperature sensitivity of stem CO2 efflux ( Q 10 ) calculated for the established periods ranged between 1.61 and 3.46 and varied over the season, with the lowest values occurring in July and August. Q 10 calculated using data from the full growing seasons ranged between 2.30 and 2.94 and was often significantly higher than Q 10 calculated for the individual periods. Temperature-normalized stem CO2 efflux ( R 10 ) determined using Q 10 from growing season data was overestimated when the temperature was below 10 °C and underestimated when the temperature was above 10 °C, compared with R 10 calculated using Q 10 established for the individual periods. The differences in daily mean R 10 calculated by these two approaches ranged between −0.9 and 0.2 μmol CO2 m −2 s −1 . The results of this study confirm that long periods for determining the temperature dependence of stem CO2 efflux encompass different statuses of the wood (especially in relation to stem growth). This may cause bias in models using this relationship for estimating stem CO2 efflux as a function of temperature.